Caracterização de células pluripotentes indiferenciadas do saco vitelino de ratas wistar diabética - Santos, José Ronaldo Alves do (2013)
Introduction: Stem cell therapy has been applied as coadjutant or treatment for some diseases or disorders. A range of sources of pluripotent cells have been investigated as placental, umbilical cord, teeth pulp, fat. However pluripotent cell behavior submitted to a concomitant physiological disorder as diabetes has been no fully understood. Methods: We aimed to evaluate proliferative potential, and the characterization of stem cells markers for potential cell differentiation, mitochondrial activity, cell cycle and apoptosis in samples of stem cells from yolk sacs obtained from rats in 15 and 20 gd in normal and hyperglycemic conditions using flow cytometry to analyze cell cycle stages, mitochondrial membrane potential, expression of Stro-1, CD90, Nanog, Oct 3/4, CD117, CD115, CD 44, CD34, VEGF-R1, COX-2, MCP-1, INF-₢ R1, L 1 and phosphorylated Caspase-3. Results: In diabetic groups we observed high levels of mitochondrial inactivity, intensively decreasing in G2/M phase, over expression of caspase, decreased expression of adhesion formation markers such as CD 44, CD 34, and NANOG. Increased pluripotency CD 90 receptor, VEGF-R1, TNF-R1, IL-1, COX-2, Caspese. Discussion: In the last period of gestation diabetes might be associated to permeability deregulation, mitochondrial integrity, cytochrome c release, reduction in the cell cycle progression, apoptosis activation and proliferative capacity decreasing. Conclusion: Diabetes seems to play a negative influence on yolk sac cell behavior in the last period of gestation.